Comparative studies of cost accounting practices in Japan and Germany / Shinsuke Wada and Peter Kajüter - Wada, Shinsuke; Peter, Kajüter (Accounting Research Institute (ARI), 2012)
This paper examines the characteristics of cost accounting in Japan and Germany and how it is embedded in the cultural, institutional and educational environment. The findings are based on an exploratory survey concerning cost accounting in medium-sized Japanese and German companies in the food and beverage, mechanical engineering as well as hospital sector. The main purpose of this project is to investigate the similarities and the differences of cost accounting practices in Japan and Germany. In particular, this paper describes the close relationships of cost accounting and cultural factors. The empirical results suggest that Japanese cost accountants are rather integrated into the Japanese management systems. Moreover, a gap between education and practice, and a diversity of career developments in the field of cost accounting are identified.